2009
DOI: 10.1007/s10462-009-9137-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in differential evolution: a survey and experimental analysis

Abstract: Differential Evolution (DE) is a simple and efficient optimizer, especially for continuous optimization. For these reasons DE has often been employed for solving various engineering problems. On the other hand, the DE structure has some limitations in the search logic, since it contains too narrow a set of exploration moves. This fact has inspired many computer scientists to improve upon DE by proposing modifications to the original algorithm. This paper presents a survey on DE and its recent advances. A class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
373
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 847 publications
(379 citation statements)
references
References 99 publications
0
373
0
6
Order By: Relevance
“…For the control parameters CR and F, there is no so called distinctive rules to set their values but the setting affects the functionality of DE [8]. For example, a large value of F increases the exploration ability but decreases the exploitation ability and vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For the control parameters CR and F, there is no so called distinctive rules to set their values but the setting affects the functionality of DE [8]. For example, a large value of F increases the exploration ability but decreases the exploitation ability and vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The nature of optimization problems such as noise and high dimensionality also affects parameter setting [8]. Higher dimensionality in an optimization problem requires higher values of NP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An EA with two evolutionary operators are designed as follows. 2) DDE with DE/rand/1 operator for feeder assignment DE/rand/1 mutation (Das and Suganthan, 2011;Neri and Tirronen, 2010) which has been indicated to be one of the most efficient operators is adopted here.…”
Section: An Ea With Two Evolutionary Operatorsmentioning
confidence: 99%
“…DE has three parameters: i) amplification factor of the differential variation, F; ii) crossover control parameter, CR; iii) population size, m. The above three operations are repeated until a termination criterion is reached. A survey with an experimental study concerned with variants of DE is found in [9]. In this section, we describe the main steps of the basic DE and a modified operation of mutation that combines three classic mutation strategies.…”
Section: Differential Evolutionmentioning
confidence: 99%